Geology and characteristics of Pb-Zn-Cu-Ag skarn deposit at Ruwai, Lamandau Regency, Central Kalimantan - Arifudin Idrus; Lucas Donny Setijadji; Fenny Tamba; Ferian Anggara (Journal of Applied Geology, 2015)
This study is dealing with geology and characteristics of mineralogy, geochemistry and physicochemical conditions of hydrothermal fluid responsible for the formation of skarn Pb-Zn-Cu-Ag deposit at Ruwai, Lamandau Regency, Central Kalimantan. The formation of Ruwai skarn is genetically associated with calcareous rocks consisting of limestone and siltstone (derived from marl?) and controlled by NNE-SSW-trending strike slip faults and localized along N 70° E-trending thrust fault, which also acts as contact zone between sedimentary and volcanic rocks in the area. Ruwai skarn is mineralogically characterized by prograde alteration (garnet and clino-pyroxene) and retrograde alteration (epidote, chlorite, calcite and sericite). Ore mineralization is characterized by sphalerite, galena, chalcopyrite and Ag-sulphides (particularly acanthite and argentite), which formed at early retrograde stage. Geochemically, SiO2 is enriched and CaO is depleted in limestone, consistent with silicic alteration (quartz and calc-silicate) and decarbonatization of the wallrock. The measured reserves of the deposit are 2,297,185 tonnes at average grades of 14.98 % Zn, 6.44 % Pb, 2.49 % Cu and 370.87 g/t Ag. Ruwai skarn orebody originated at moderate temperature of 250-266 °C and low salinity of 0.3-0.5 wt.% NaCl eq. The late retrograde stage formed at low temperature of 190-220 °C and low salinity of ~0.35 wt.% NaCl eq., which was influenced by meteoric water incursion at the late stage of the Ruwai Pb-Zn-Cu-Ag skarn formation. Keywords: Geology, skarn, mineralogy, geochemistry, Ruwai, Central Kalimantan